ChemInform Abstract: Synthesis of New Azocompounds and Fused Pyrazolo[5, 1‐c][1, 2, 4]triazines Using Heterocyclic Components. Issue 47 (4th November 2013) - Ledenyova, Irina V.; Didenko, Vitaly V.; Shestakov, Alexander S.; Shikhaliev, Khidmet S.
Abstract All products are purified by either recrystallization or simple washing.